An understanding of the prostate cancer pathophysiology for identification of biomarkers that support an early diagnosis (2018)
Prostate Cancer (CaP) is a condition whose etiology is multifactorial, it goes through genetic, infectious, as well as environmental, among others. Currently, PCa represents the most frequent cancer among men and the second in mortality, however, there are still multiple gaps in the knowledge of this condition. One of them is related to a molecular biomarker that allows early and accurate diagnosis of PCa. We have the Prostate Specific Antigen (PSA), however, its diagnostic performance alone is very low, and it must always be associated with digital rectal examination to obtain the best of both diagnostic methods.